Applications of Fat Grafting in Pediatric Patients - Shih, Linden; Abu-Ghname, Amjed; Davis, Matthew J.; Xue, Amy S.; Dempsey, Robert F.; Buchanan, Edward P. (Seminars in Plastic Surgery, 2020)
Autologous fat grafting has become a widely utilized technique for a variety of cosmetic and reconstructive procedures. Its potential for volume restoration and tissue regeneration has made it a popular method for treating soft tissue defects in both adult and pediatric populations. While autologous fat grafting in the pediatric setting is not as well characterized as it is in the adult setting, various reports have demonstrated the safety and utility of its applications in nonadult patient populations. In this article, we present the first comprehensive review of the current applications of autologous fat grafting in pediatric patients. Specific challenges to fat grafting in the pediatric setting and future applications will also be discussed.
Keywords: pediatric fat grafting; autologous fat grafting; pediatric lipofilling; volume restoration; congenital tissue deficiency; velopharyngeal insufficiency; scars